Evaluasi perkembangan lengkungrahanganaksebelum dansesudah penggunaan pirantiortodontiklepasan (Evaluation of the jaw arch development in children before and after using removable orthodontic appliance) - Sherly Horax; Asnidar Asnidar (DiscoverSys Inc., 2015)
Orthodontics is one science that evaluates the development and growth of the child masticatory system in order to achieve a harmonious face shape and adequate chewing function. This study is aimed to evaluate the development of thejaw arch in children before and after using removable orthodontic appliance through model of the patient's teeth in theDental Hospital, Faculty of Dentistry, University of Hasanuddin. At this descriptive observational study, sample met thecriteria as much as 33 models of patients aged 13-19 years old were measured by the Ponts, Kesling and Howes index.According to Ponts Index, based on the width of the anterior arch, enlarged jaw72.7%and 15.1%decreases; while basedon the width of the posterior arch, enlarged jaw jaw 69.7% and 12.1% decreases. According to Kesling Index, based on right jaw, enlarged by 84.8%and9.1%smaller jaw; based on left jaw, enlarged by 87.8% and 6.1% smaller jaw.Accordingto Howes Index, interpremolar enlarged shrinking 75.8% and 21.2%. According to Howes Index, large apical baseenlarged shrinking 81.8% and 12.1%. It was concluded that the use of different removable orthodontic device affects thedevelopment and growth of the child's jaw.